Isolation, pharmacological activity and structure determination of physalin B and 5β, 6β‐epoxyphysalin B isolated from Congolese Physalis angulata L. (15th December 2013) - Mangwala Kimpende, Peter; Lusakibanza, Mariano; Mesia, Kahunu; Tona, Lutete; Tits, Monique; Angenot, Luc; Frédérich, Michel; Van Meervelt, Luc
<x xml:space="preserve">Abstract</x> Physalis angulata L., an annual herb from the Solanaceae family, is widely used in popular medicine in tropical countries to treat a variety of diseases. Two products, (X) and (Y), were isolated from a crude CH2Cl2 extract of dried Congolese Physalis angulata L. plants and crystallized from acetone for structure elucidation. Compound (X) corresponds to a physalin B dimer acetone solvate hydrate (2C28H30O9·C3H6O·0.22H2O), while compound (Y) crystallizes as a mixed crystal containing two physalin B molecules which overlap with 5β, 6β‐epoxyphysalin B, also known as physalin F, and one acetone molecule in the asymmetric unit (1.332C28H30O9·0.668C28H30O10·C3H6O). Antiplasmodial activity, cytotoxic activity and selectivity indices were determined for crude extracts and the two isolated products (X) and (Y).